2020
DOI: 10.1177/1071100720962411
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive vs Open Akin Osteotomy

Abstract: Background: Minimally invasive techniques of Akin osteotomy have grown in popularity, as early results suggest faster recovery, earlier return to work, and minimized wound healing problems. Preserving lateral cortex integrity during first phalanx osteotomy thereby presents a challenge because of the lack of direct visual control. This retrospective comparative study investigated clinical and radiographic outcomes of minimally invasive and open Akin osteotomy with different fixation methods and analyzed whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Subsequently, reliable and reproducible 2D measures of HV severity such as the hallux valgus angle and intermetatarsal angle were developed and are still used ubiquitously today. 2,16,17,21,27,36,46 Further, numerous operations to normalize these quantitative measures of HV deformity also exist. 9,16,46 Despite the use of these 2D quantitative measures and operative correction of sagittal and transverse plane deformities, consistent rates of poor outcomes and HV recurrence persist with operative correction.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, reliable and reproducible 2D measures of HV severity such as the hallux valgus angle and intermetatarsal angle were developed and are still used ubiquitously today. 2,16,17,21,27,36,46 Further, numerous operations to normalize these quantitative measures of HV deformity also exist. 9,16,46 Despite the use of these 2D quantitative measures and operative correction of sagittal and transverse plane deformities, consistent rates of poor outcomes and HV recurrence persist with operative correction.…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up times were highly variable, ranging from 6 months to 7 years. Among the included studies, 8 studies ( 15 , 17 , 24 , 26 , 28 , 29 , 31 , 35 ) were RCTs, 2 studies ( 4 , 14 ) were prospective comparative studies, and 12 studies ( 5 , 13 , 16 , 18 , 22 , 23 , 25 , 27 , 30 , 32 34 ) were retrospective comparative studies. A total of 10 studies ( 13 , 17 , 22 28 , 32 ) reported on the 2G percutaneous hallux valgus surgery, in which 7 studies ( 13 , 22 25 , 28 ) involved Bösch osteotomy and 3 studies ( 17 , 26 , 27 ) involved a simple, an effective, a rapid, and an inexpensive (SERI) technique.…”
Section: Resultsmentioning
confidence: 99%
“…Siddiqui et al ( 32 ) performed a retrospective comparison between Bösch and Chevron surgery. Nine studies ( 5 , 14 16 , 18 , 29 , 30 , 34 , 35 ) reported on the 3G percutaneous hallux valgus surgery, including percutaneous chevron–akin (PECA) and MICA. Brogan et al ( 5 ) performed a retrospective study to compare between the PECA and Chevron technique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four feet also underwent capsulotomy, collateral ligaments release and extensor tendon lengthening of the metatarsophalangeal joint for dorsal dislocation of clawed lesser toes. No other additional surgeries such as Akin, 16 Weil, 17 or other lesser metatarsal osteotomies was performed.…”
Section: Methodsmentioning
confidence: 99%